2014
DOI: 10.1007/s11633-014-0824-3
|View full text |Cite
|
Sign up to set email alerts
|

Selection of suitable maximum-heart-rate formulas for use with Karvonen formula to calculate exercise intensity

Abstract: Abstract:The Karvonen formula, which is widely used to estimate exercise intensity, contains maximum heart rate, HRmax, as a variable. This study employed pedaling experiments to assess which of the proposed formulas for calculating HRmax was the most suitable for use with the Karvonen formula. First, two kinds of experiments involving an ergometer were performed: an all-in-one-day experiment that tested eight pedaling loads in one day, and a one-load-per-day experiment that tested one load per day for eight d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 11 publications
0
29
0
5
Order By: Relevance
“…We first cleaned the data and used linear interpolation on steps, heart rate, calories, and floors climbed to impute missing data. Following this, we developed a feature set that included intensity (Karvonen Formula) 26,27 which calculates individualized target heart rate parameters, steps entropy, which is a measure of predictability of step count, and correlation coefficient between heart rate and steps 28 . We developed the features in order to consider multiple physiological characteristics that could explain sedentary, light, moderate, and vigorous physical activity (See Table 1).…”
Section: Analysesmentioning
confidence: 99%
“…We first cleaned the data and used linear interpolation on steps, heart rate, calories, and floors climbed to impute missing data. Following this, we developed a feature set that included intensity (Karvonen Formula) 26,27 which calculates individualized target heart rate parameters, steps entropy, which is a measure of predictability of step count, and correlation coefficient between heart rate and steps 28 . We developed the features in order to consider multiple physiological characteristics that could explain sedentary, light, moderate, and vigorous physical activity (See Table 1).…”
Section: Analysesmentioning
confidence: 99%
“…Most studies determine %HRR based on typical activity patterns and experimental environments, and there are very few cases that consider an actual construction site. Concerning the application of methods for determining %HRR of construction workers, it is difficult to measure HR max and HR resting [ 59 , 60 , 61 ] in advance for workers, and it is likely that %HRR will interfere with actual use as the indicators.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental intervention involved 20 min of aerobic exercise on a stationary bicycle. After 5 min of walking to warm-up, the patients were asked to perform 20 min of moderate exercise on the bicycle at 60% to 80% of their target heart rate, calculated using the Karvonen formula [ 45 ]. The duration of exercise was based on previous studies, which reported that 15 to 20 min of exercise has a positive impact on cognition [ 41 , 46 ].…”
Section: Methodsmentioning
confidence: 99%